Endowment as a Fundraising Tool of the Research University - Stepanova, Alla; Horbas’, Iryna; Derkach, Oksana; Ovcharenko, Tetyana (European Journal of Sustainable Development, 2020)
The article summarizes the arguments within the scientific discussion about the search of alternative sources of research universities funding in the absence of sufficient support from the government. The main objective of the research is to define the possibility of using the endowment as a fundraising tool to attract alternative sources of funding for research universities in Ukraine. The relevance of solving this scientific issue lies in the fact that modern research universities are independent entities, which according to the Bologna Declaration assume the entire load on the future of the state and have to do it at the highest professional level. This can be ensured through a combination of traditional and modern sources of funding. The world experience of successful implementation of the endowment has been presented. The level of knowledge intensity of GDP, which is one of the key indicators that reflects the level of quality of higher education, has been analyzed. The endowment as one of the most effective fundraising tools is poorly developed in Ukraine. This fact has prompted us to research the main provisions of this phenomenon and to define the conditions for its implementation in Ukrainian research-based institutions of higher education by means of the strategic analysis. The conducted SWOT analysis has made it possible to systematize problem areas of the domestic market of educational services in the direction of creating and using the endowment and predicting possible strategies for its development. Since the Research Universities are considered to be the core of creation of intellectual and innovative products and the crucial mover of scientific and technological progress in the country and in the world, they have been chosen as the research object. Keywords: fundraising, endowment, Research University, market of educational services, investment, alternative sources of funding